Synergistic chiral iminium and palladium catalysis: Highly regio- and enantioselective [3 + 2] annulation reaction of 2-vinylcyclopropanes with enals - Zhu, Haipan (Beilstein J Org Chem, 2016)
A cooperative catalytic strategy of chiral iminium catalysis by regioselective activation of the C=C bond in enals and a transition metal promoting to open the 2-vinylcyclopropanes for highly regio- and enantioselective [3 + 2] cycloaddition reaction of 2-vinylcyclopropanes with α,β-unsaturated aldehydes has been developed.